Tangled up in you [large type] - Lauren, Christina (Meant to be novel, 2024)
"Ren has never held an iPhone, googled the answer to a question, or followed a crush on social media. What she has done: read a book or two, or three (okay, hundreds). Taught herself to paint. Built a working wind power system from scratch. But for all the books she's read, Ren has never found one that's taught a woman raised on a homestead and off the grid for most of her twenty-two years how to live in the real world. So when she finally achieves her lifelong dream of attending Corona College, it feels like her life is finally beginning. Fitz has the rest of his life mapped out: graduate from Corona at the top of his class, get his criminal record wiped clean, and pass himself off as the rich, handsome player everyone thinks he is. He's a few months short from checking off step one of his plans when Ren Gylden, with her cascading blonde hair and encyclopedic brain, crashes into his life, and for the first time Fitz's plan is in jeopardy. But a simple assignment in their immunology seminar changes the course of both their lives, and suddenly they're thrown out of the frying pan and into the fire on a road trip that will lead them in the most unexpected directions. Out on the open road, the world somehow shifts, and the unlikely pair realize that, maybe, the key to the dreams they've both been chasing have been sitting next to them the whole time." --